Teaching and learning experience with a virtual classroom in the field of pedagogical support due to covid-19 - Leda Beatriz Digión; Margarita María Álvarez (Universidad de Guadalajara, 2021)
This work describes a pedagogical proposal for the dictation of a degree course, which originally had a face-to-face modality, sustained with the e-learning modality in the 2020 school year due to the social health situation caused by Covid-19. An analytical framework based on the pedagogical model of dimensions was applied, adapted for the virtual design of the Medical Informatics subject, of the Medicine career of the National University of Santiago del Estero, Argentina. The proposed dimensioning in the field of the pedagogical accompaniment process projected by the authorities of the faculty, allowed to program the active participation of the students and organize the monitoring of learning, through the axes proposed by the chair: individual work, group work, interactions and interventions. Regarding the results obtained on educational mediation in the virtual classroom, it was possible to identify and propose the guidelines and resources in a new pedagogical dimension on didactic strategies; thus, this proposed dimension is considered a highly usable component for teaching work in search of an autonomous student, in terms of achieving goals in their teaching and learning process, as shown by the presented experience.